The Effect of Transformational Leadership on Employee Job Performance through Mediating Role of Organizational Commitment in Logistic Sector of Pakistan - Altaf Hussain; Rosman Md Yusoff; Muhammad Asad Khan; Mohd Lizam Mohd Diah; Muhammad Saeed Shahbaz (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to examine the effect of transformational leadership on the employee job performance through organizational commitment in the logistics sector of Pakistan. Data were collected from the employees of logistic sectors headquarter, Islamabad througha self-administered questionnaire usingpurposive sampling technique. 280 self-administered questionnaires were distributed among the employees of PTCL but 210 questionnaires were returned observing response rate as 75 %. Data were analyzed using structural equational modeling (SEM). Results of the study indicate that transformational leadership has both the direct significant effect on employee job performance and also the indirect significant effect on employee job performance through organizational commitment. In the light of the findings of this research, it is recommended for PTCL management to adopt a transformational leadership style to cope with todays fast changing environment.